2018
DOI: 10.1002/jcp.26903
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐499 regulates myoblast proliferation and differentiation by targeting transforming growth factor β receptor 1

Abstract: MicroRNAs (miRNAs or miRs) are small noncoding RNAs that play critical roles in muscle cell proliferation and differentiation via post-transcriptional regulation of gene expression. Here, based on our previous high-throughput sequencing results, we evaluated miRNA-499 (miR-499) functions during myoblast proliferation and differentiation. In addition, we analyzed miR-499 expression profiles and characterized the associated functional roles. MiR-499 is known to be a skeletal muscle fiber-type-associated miRNA. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The present study demonstrated that miR-499-5p injection signi cantly decreased the diameter of muscle ber. The result was consistent with the previous studies because the diameter of slow-twitch muscle ber was smaller than fast-twitch muscle ber and miR-499-5p could regulate skeletal myo ber speci cation [9,15,19,20]. However, little is known about the metabolic change of miR-499-5p involvement in the process.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study demonstrated that miR-499-5p injection signi cantly decreased the diameter of muscle ber. The result was consistent with the previous studies because the diameter of slow-twitch muscle ber was smaller than fast-twitch muscle ber and miR-499-5p could regulate skeletal myo ber speci cation [9,15,19,20]. However, little is known about the metabolic change of miR-499-5p involvement in the process.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, miRNAs have been shown to regulate gene expression and be involved in the proliferation and differentiation of skeletal muscle [18]. Previous evidence has indicated that miR-499-5p regulated skeletal myo ber speci cation by targeting Sox6 [15,19], Rod1 [19], Thrap1 [9], and TGFβR1 [20]. It was found in our previous study that miR-499-5p levels in skeletal muscle were decreased accompanied by increasing age.…”
Section: Discussionmentioning
confidence: 70%
“…The targeted knockout of TAK1 caused increased oxidative stress and dysfunctional regeneration in response to muscle injury 14 . By contrast, many studies have shown that TAK1 activators inhibit myogenic differentiation, 42–44 implying that TAK1 is a negative regulator of differentiation. Moreover, other studies have indicated that TAK1 overexpression can increase proliferation and reduce differentiation 23,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, selected miRNAs have been demonstrated to inhibit the myogenic differentiation acting on TGFβ and Wnt/β-catenin signaling. The myomiR miR-499 may inhibit TGFβ-receptor 1, promoting the proliferation of C2C12 cells [87], whereas miR-216a targets Smad7, a member of the inhibitory Smads family that can specifically inhibit TGFβ pathway and bovine primary muscle cells differentiation [88]. Inhibition of cell self-renewal progression of muscle precursors in the myogenic lineage has been attributed to miR-143-3p and miR-664-5p that downregulate Wnt5a, LRP5, Axin2, β-catenin and Wnt1 expression [89,90].…”
Section: Mirnas Role In Myogenesismentioning
confidence: 99%